Efficacy of liposomal amphotericin against febrile neutropenia in pediatric patients receiving prophylactic voriconazole. Issue 5 (27th March 2021) - Kobayashi, Ryoji; Matsushima, Satoru; Hori, Daiki; Sano, Hirozumi; Suzuki, Daisuke; Kishimoto, Kenji; Nakano, Takaaki; Yanagi, Masato; Kodama, Kouya; Kobayashi, Kunihiko
Abstract: Background: The risk factors for invasive fungal infection have gradually become evident for pediatric patients with hematological diseases. Here we analyze the efficacy of liposomal amphotericin (L‐AMB) for pediatric patients with febrile neutropenia using prophylactic voriconazole (VRCZ). Method: We administered L‐AMB (2.5 mg/kg/day) in patients with febrile neutropenia who were receiving prophylactic VRCZ (10 mg/kg/day, orally) and were resistant to second‐line antibiotics therapy. Thirteen patients (5 males, 8 females) with 19 febrile neutropenia episodes were targeted in this analysis. The median age of the patients was 14 years (range, 1–19 years). Eighteen out of 19 episodes occurred in patients with acute myeloid leukemia, with the remaining episode occurring in a patient with acute unclassified leukemia. Results: The median period from start of L‐AMB administration to resolution of fever was 4 days (1–27 days). In 15 out of 19 episodes, fever resolved within 5 days from commencement of L‐AMB administration. Using criteria proposed by T. J. Walsh et al., the success rate of L‐AMB for febrile neutropenia was 89.5% in this study. Conclusions: Although the sample size of our study was small, the extremely high efficacy of L‐AMB warrants its administration in patients with febrile neutropenia who are receiving VRCZ.